Examining the effect of Debris Flow on Oil and Gas Pipelines Using Numerical Analysis - Mustaffa, Zahiraniza; Al-Bared, Mohammed A.M.; Habeeb, Nursyahira; Khan, Mudassir A. (Global Journal of Earth Science and Engineering, 2022)
This article examines the impact of debris flow on semi-exposed pipelines to determine the plastic deformation and stresses by considering pipe-debris flow interaction. A 3-D finite element approach was adopted to study the mechanical behavior of pipelines subjected to debris flow. Integration of pipeline property (thickness) with debris flow intensity (impact pressure and angle) was also considered in a finite element numerical model for semi-exposed. The analysis showed that the impact angle between 35° and 75° with an impact pressure of 200 kPa and 250 kPa significantly affected the stability and integrity of the pipeline. There was a slight impact of wall thickness on the stability of the pipeline due to the passive soil resistance. Maximum plastic deformation of 124 mm was encountered in the case of 35° impact angle, which was 3% more than the deformation observed at 20° impact angle. Moreover, large distribution of von mises stresses was observed, as 1390 Mpa, 1450 Mpa, 1440 Mpa, and 1440 Mpa for impact angles of 20°, 35°, 75°, and 90° in the impacted zone of the pipeline in each set of analysis. Shear failure of the pipeline was observed during the analysis as von misses’ stresses were more than the yield stress (520 Mpa) of the pipeline. The developed model in this study can be utilized for further research and will be a basis for designing pipelines crossing through mountainous regions.